Evidence for Polyadenylated mRNA in Pseudomonas aeruginosa - Saravanamuthu, Senthil Selvan (American Society for Microbiology, 2004)
In this paper, we report the synthesis of Pseudomonas aeruginosa cDNA in the presence of oligo(dT) primers. Hybridization of oligonucleotide DNA microarrays indicates that under the experimental conditions used, at least 43.7% of the expressed genes from P. aeruginosa PAO1, representing many different functional classes, can be detected by using oligo(dT)-primed cDNAs.